Influence of accessory sulci of the frontoparietal operculum on gray matter quantification - Vallejo-Azar, Mariana N.; Alba-Ferrara, Lucia; Bouzigues, Arabella; Princich, Juan P.; Markov, Martin; Bendersky, Mariana; Gonzalez, Paula N. (Frontiers in Neuroanatomy, 2023)
Introduction: The perisylvian region is the cortical core of language and speech. Several accessory sulci have been described in this area, whose presence could modify the results of the automatic quantification of gray matter by popularly used software. This study aimed to assess the expression of accessory sulci in the frontoparietal operculum (FPO) and to evaluate their influence on the gray matter volume estimated by an automatic parcellation of cortical gyri and sulci. Methods: Brain MRI scans of 100 healthy adult volunteers were visually analyzed. The existence of the triangular and diagonal sulci, and the number of accessory sulci in the frontoparietal operculum, were assessed on T1 images. Also, the gray matter volume of gyri and sulci was quantified by an automatized parcellation method. Interhemispheric differences in accessory sulci were evaluated with Chi-square and Wilcoxon paired tests. The effects of the hemisphere, sex, age, total intracranial volume, and accessory sulci on morphometric variables were assessed by linear models. Results: These sulci were found in more than half of the subjects, mostly in the left hemisphere, and showed a significant effect on the gray matter content of the FPO. In particular, the volume of the inferior frontal sulcus, pars opercularis of the inferior frontal gyrus, horizontal ramus of the lateral sulcus, angular gyrus, and postcentral gyrus showed a significant influence on the presence of accessory sulci. Discussion: The prevalence of tertiary sulci in the FPO is high, although their meaning is not yet known. Therefore, they should be considered to reduce the risk of misclassifications of normal variation.